A study on preparation of ultra-thin localized Au coating by laser-induced electrodeposition. (October 2022) - Guo, Sheng; Xu, Kun; Wu, Yucheng; Shen, Wenrong; Zhu, Hao; Liu, Yang; Zhang, Zhaoyang
Graphical abstract: Highlights: Laser irradiation realizes ultra-thin localized Au Coating. Laser irradiation increases the electrodeposition efficiency. Laser irradiation improves the surface quality of Au coating. Laser irradiation achieves precise regulation of dimensional accuracy. Laser irradiation improves corrosion resistance of Au coating. Abstract: Traditional electrodeposition requires auxiliary technologies such as mask to realize localized deposited layer. In this paper, ultra-thin Au coating can be obtained selectively by laser-induced electrodeposition without mask, which has advantages in dimensional accuracy, brightness, good compactness. The deposition rate, dimensional accuracy, density, roughness, and corrosion resistance were evaluated under different laser single pulse energy (4.5, 5, 5.5, 6, 6.5, 7, 7.5, and 8 μJ). Furthermore, the spatial distribution of the transient temperature field and the change law of the cathode substrate current under laser irradiation were detected to explore the mechanism induced by laser thermal effect. The results show that laser irradiation can increase the cathode limit current density to reach the Au precipitation potential. Besides, the electrodeposition rate increases with the increase of laser single pulse energy. When the laser single pulse energy is 6 µJ, the electrodeposition rate reaches 0.167 mg/min. Meanwhile, the electrodeposition accuracy and surface density are better, and surface roughness (Sa) is 0.98 μm. Moreover, compared with the Au coating product provided by an electroplating enterprise, the coating prepared by laser-induced electrodeposition has better corrosion resistance. When the laser single pulse energy is 6 µJ, self-corrosion potential (φcorr ) is −0.3059 V, and self-corrosion current density (jcorr ) is 5.066 × 10 −5 A/cm 2 .